‘Etsi peccaui, sum tamen ipse tuus’. O elegii pokutnej Drakoncjusza (i słówko o pojęciu: barokowa ‘elegia’ pokutna) - Wasyl, Anna Maria (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
Dracontius’s Satisfactio, though undoubtedly a prime example of a very complex literary work, is not really a work that cannot be properly described in generic terms. Upon consideration, the label ‘penitential elegy’ appears to be the most appropriate one, as it clearly indicates the major theme of the poem (the contrition of the sinner who acknowledges his sin above all before the God and, in the second place, before the Vandal king Gunthamund, to whom he pleads guilty to some not fully specified misdeed) as well as its metrical form. As for the latter, what is of particular relevance is not merely the fact that the piece is composed in elegiac couplets, but also that it is clearly written with an eye on Ovid the elegist. It is above all Ovid’s exilic motifs that Dracontius reuses throughout his poem, with special focus on Tristia II, imitated not so much through explicit verbal echoes, but rather through the general analogy of poetic situations in which the punished poet openly addresses his punisher, the princeps (Dracontius ostentatiously cites this ‘Ovidian’ word). At times, Dracontius happens to be no less provocative than Ovid was in apostrophizing his powerful addressee, although adopting a protreptic tone (which naturally implies some sort of superiority to the literary ‘you’), he does not pose as an expert in poetry with blemish life, despite his musa iococa (as Ovid did), but as a ‘fellow-Christian’ (suppressing all doctrinal discrepancies between his own Catholicism and Gunthamund’s Arianism) and indeed: a ‘fellow-sinner’ who forgives his (royal) ‘brother’ and asks for forgiveness in return. Moreover, the penitential tone of the poem is also stressed by several references to the Psalms and in particular to the figure of King David doing penance, exactly as in the Polish Baroque penitential elegy. The generic label I have advocated throughout my article is, in fact, ‘borrowed from’ the students of Old-Polish poetry, who are virtually unanimous in recognizing Baroque penitential elegy as a separate literary subgenre. It is not my intention to argue against such conclusions, as the generic features indicated by those specialist are quite convincing (I myself have found them very helpful for my own research), yet what I do emphasize is the very fact that the term ‘elegy’ when referred to vernacular poetry is applied not strictly (it is not related to any specific meter) but rather metaphorically, as if merely pointing to a general ‘mood’ of a poem. In Latin poetry, however, ‘elegy’, meaning ‘automatically’ the elegiac distich, means also concrete intertextual associations, primarily with Ovid (precisely like in Dracontius’s Satisfactio). Hence, when used to describe Dracontius’s text, the label ‘penitential elegy’ reveals its full hermeneutic potential.